Extracellular vesicles secreted by triple‐negative breast cancer stem cells trigger premetastatic niche remodeling and metastatic growth in the lungs. Issue 10 (7th February 2023) - González‐Callejo, Patricia; Gener, Petra; Díaz‐Riascos, Zamira V.; Conti, Sefora; Cámara‐Sánchez, Patricia; Riera, Roger; Mancilla, Sandra; García‐Gabilondo, Miguel; Peg, Vicente; Arango, Diego; Rosell, Anna; Labernadie, Anna; et al.
Abstract: Tumor secreted extracellular vesicles (EVs) are potent intercellular signaling platforms. They are responsible for the accommodation of the premetastatic niche (PMN) to support cancer cell engraftment and metastatic growth. However, complex cancer cell composition within the tumor increases also the heterogeneity among cancer secreted EVs subsets, a functional diversity that has been poorly explored. This phenomenon is particularly relevant in highly plastic and heterogenous triple‐negative breast cancer (TNBC), in which a significant representation of malignant cancer stem cells (CSCs) is displayed. Herein, we selectively isolated and characterized EVs from CSC or differentiated cancer cells (DCC; EVs CSC and EVs DCC, respectively) from the MDA‐MB‐231 TNBC cell line. Our results showed that EVs CSC and EVs DCC contain distinct bioactive cargos and therefore elicit a differential effect on stromal cells in the TME. Specifically, EVs DCC activated secretory cancer associated fibroblasts (CAFs), triggering IL‐6/IL‐8 signaling and sustaining CSC phenotype maintenance. Complementarily, EVs CSC promoted the activation of α‐SMA+ myofibroblastic CAFs subpopulations and increased the endothelial remodeling, enhancing the invasive potential of TNBC cells in vitro and in vivo. In addition, solely the EVs CSC mediated signaling prompted the transformation of healthy lungs into receptive niches able to support metastatic growth of breast cancer cells. Abstract : What's new? Cancer‐secreted extracellular vesicles (EVs) are involved in premetastatic niche (PMN) conditioning, which promotes disease spread. However, diversity among cancer‐secreted EVs, which is related to heterogeneity in tumor cells, often is disregarded in the context of cancer progression. Here, the authors examined the activity of cancer cell‐secreted EVs in triple‐negative breast cancer (TNBC) at distinct states of tumor cell differentiation. Experiments show that EVs differ radically in their activities, depending on their original cancer cell subtype. Specifically, signaling systems involving EVs secreted by cancer stem cells were found to drive PMN remodeling in TNBC models, both in vitro and in vivo.